Profil Kemampuan Objek Kontrol Siswa Usia 7-9 Tahun di Sekolah Dasar Negeri 14 Limo Kaum Batusangkar - Irsanul Fauzi; Syahrial Bakhtiar; Jonni, Jonni; Sepriadi, Sepriadi (Mutiara Pendidikan dan Olahraga, 2025)
The problem in this study is the ability of the control object of students at Elementary School 14 Limo Kaum Batusangkar which is still relatively low, this is thought to be caused by many factors. The purpose of this study was to determine the profile of the control object ability of students at Elementary School 14 Limo Kaum Batusangkar. This type of research is descriptive which aims to reveal how the description of the basic movement skills of the control object in students at Elementary School 14 Limo Kaum Batusangkar during the research period from November to January 2025. The place of this research was at Elementary School 14 Limo Kaum Batusangkar. The population in this study were all students at Elementary School 14 Limo Kaum Batusangkar totaling 159 people. The sampling in this study used the Proportional Stratified Random Sampling technique, so that the sample in this study amounted to 32 people. The data collection technique was using the 2nd edition of the Test Of Gross Motor Development or TGMD-2. The data analysis technique used descriptive analysis techniques. Based on the research that the researcher has conducted, it can be concluded that the Control Object Ability Profile of Students Aged 7-9 Years at State Elementary School 14 Limo Kaum Batusangkar has an average of 16.19 or 31% who have object control abilities or are in the "less" classification.